86.9k views
5 votes
Raul used the steps shown below to solve the equation. In which step did Raul make a mistake?

5x-3(2x+7)=2x+9
Step 1: 5x-6x-21=2x+9
Step 2: -11x-21=2x+9
Step 3: -12x=30
Step 4: x=-30/12

A. Step 1
B. Step 2
C. Step 3
D. Step 4

User Clawesome
by
5.9k points

2 Answers

3 votes
I believe a mistake was made on step 2.
User Andycam
by
6.5k points
0 votes

5x-3(2x+7)=2x+9

This is the equation and Raul had to solve it for x

So he started with simplifying the parenthesis first

To simplify the parenthesis -3 gets multiplied with 2x and 7 , to get rid of parenthesis

So it came out to be

5x-3(2x+7)=2x+9

STEP-1

5x-6x -21 = 2x+9 , So the STEP-1 is correct,

After this in Step -2 , he has combined the like terms on left side, the like terms are 5x and -6x , 5x-6x should combine to -x , because 5-6 = -1

So

STEP-2

-x -21 = 2x+9 , So STEP -2 is INCORRECT

So he made a mistake in STEP-2

After that subtract 2x from both sides

-3x -21 = 9

add 21 to both sides

-3x = 30

divide both sides by -3

x=-10



Hence Option B is correct , he made a mistake in STEP -2

User John Godspeed
by
5.8k points